Antarctica [videorecording (DVD)] : a year on ice - Powell, Anthony (Documentary film director) (Music Box Films, 2015)
A visually stunning journey to the end of the world with the hardy and devoted people who live there year-round. The research stations scattered throughout the continent host a close-knit international population of scientists, technicians and craftsmen. Isolated from the rest of the world, enduring months of unending darkness followed by periods when the sun never sets, Antarctic residents experience firsthand the beauty and brutality of the most severe environment on Earth.